Towards a discursive approach to adaptation: the plan-statement, minimum unit of cinematic discourse - Segura Tornero, Alfredo (Escritura e Imagen, 2023)
This article aims to develop of a comparative method between literature and cinema based on the analysis of the speeches of Jean-Michel Adam (2008). For this purpose, it was necessary to create new cinematographic discursive categories, the minimum unit of which I will present, namely the outline.With a textual or cinematographic format, literary narratology is part of a whole - the discourse - which brings together different textual genres, and which could also apply to audiovisual events. If Gérard Genette (1989) had transformed the science of narrative into an autonomous discipline, it would now be necessary to introduce it into another much larger science. Having said that, we consider that narratology incorporates discourse and, furthermore, that cinema is a type of discourse.The minimum unit of cinematic discourse will be the plan-statement. In the act itself of the filmic enunciation, a person responsible for looking is always present, he has an enunciative control and observes what is represented with a very precise intention. In other words, an enunciative dimension which contains a perspective constructed verbally from a reference content thus creating an argumentative potential and producing an unspoken force.The stated plan is formed by these three mutually supportive and complementary components and can only exist with other stated plans and give rise to higher categories. The plan would thus be a segmentation unit while the plan-statement is a union unit. The plan will be placed in the grammatical level: the plan-set out in the speech. The model will be illustrated from a sequence of the film by Max Ophuls Le Plaisir (1952).
Keywords: literature; cinema; adaptation; discursive categories; plan-statement